PERSEPSI MAHASISWA DAN TENAGA KEPENDIDIKAN TENTANG PERILAKU CARING MAHASISWA DALAM PROSES PEMBELAJARAN DI FAKULTAS KEPERAWATAN UNPAD - Lumbantobing, Valentina; Praptiwi, Atlastieka; Susilaningsih, Sri; Adistie, Fanny (STIKes Maharani Malang, 2019)
Introduction: Nurses are expected to be able to behave caring in each service delivery to clients. Caring behavior can be emphasized and trained early. Nursing students who are prepared to become prospective nurses who are professional have been provided with knowledge about caring. Caring behavior during education can be seen from the learning process both in class, tutorial and practicum. The existence of complaints related to student behavior from several circles in the nursing faculty made the researchers look deeper into student caring behavior. The purpose of this study was to identify caring behavior of nursing students during the learning process both tutorials and practicums which were perceived by students and educational staff in the Faculty of Nursing Unpad. . Methods: This type of research is quantitative descriptive research. The population in this study were students of the nursing faculty and education staff obtained by purposive sampling. Caring behavior of nursing students is measured using the Caring Behavior Inventory questionnaire. Results and Analysis: The study of 57 students and 27 education staff as respondents showed that caring behavior of nursing students during the learning process prescribed by students was in the category (57.89%), while the perception of education staff found that student behavior in the learning process was lacking (51.85%). Discuss: It can be concluded that the caring behavior of nursing students in the learning process still needs to get special attention. One effort to improve and improve the caring behavior of nursing students is to show good role models in the student environment, as well as improve student support groups to remind each other.